Особливості розвитку української архівної періодики на початку 1990–х рр - Ковтун, М. (Архіви України, 2009)
The course of the scientific readings devoted to the former head of the archival branch of Ukraine V. Ivanenko (1933–2008) is reflected in the column. There given texts of archival establishments employees and members of “The Chernigiv community in Kiev” papers reflecting the basic aspects of V. Ivanenko’s activity.